Resensitization of TRPV1 channels after the P2 receptor activation in sensory neurons of spinal ganglia in rats - Petrushenko, Olena A.; Stratiievska, Anastasiiya O.; Petrushenko, Mariia O.; Lukyanetz, Elena A. (Frontiers in Cellular Neuroscience, 2023)
TRPV1 channels are responsible for detecting noxious stimuli such as heat (>43˚C), acid, and capsaicin. P2 receptors are involved in numerous functions of the nervous system, including its modulation and specifically responding to the application of ATP. In our experiments, we investigated the dynamics of calcium transients in DRG neurons associated with TRPV1 channel desensitization and the effect of P2 receptors activation on this process. We used DRG neurons after 1–2 days of culture to measure calcium transients by microfluorescence calcimetry using the fluorescent dye Fura-2 AM. We have shown that DRG neurons of small (d< 22 μm) and medium (d = 24-35 μm) size differentiate in the expression of TRPV1. Thus, TRPV1 channels are mainly present in small nociceptive neurons (59% of the studied neurons). Short-term sequential application of the TRPV1 channel agonist capsaicin (100 nM) leads to desensitization of TRPV1 channels by the type of tachyphylaxis. We identified three types of sensory neurons based on responses to capsaicin: 1) desensitized 37.5%, 2) non-desensitized 34.4%, and 3) insensitive 23.4% to capsaicin. It has also been shown that P2 receptors are present in all types of neurons according to their size. However, the responses of the neurons were different. Applying ATP (0.1 mM) to the intact cell membrane after the onset of tachyphylaxis caused recovery of calcium transients in response to the addition of capsaicin in these neurons. The amplitude of the capsaicin response after reconstitution with ATP was 161% of the previous calcium transient in response to capsaicin. Significantly, the restoration of the amplitude of calcium transients under the ATP application is not associated with changes in the cytoplasmic pool of ATP because this molecule does not cross the intact cell membrane, so our results show the interaction between TRPV1 channels and P2 receptors. It is important to note that the restoration of the amplitude of calcium transients under the influence of ATP was observed mainly in the cells of the 1st-2nd days of cultivation. Thus, the resensitization of capsaicin transients after P2 receptors activation may be associated with the regulation of the sensitivity of sensory neurons.